ANALISIS DESAIN PERKERASAN JALAN PANTAI AMAL LAMA KOTA TARAKAN MENGGUNAKAN METODE ANALISA KOMPONEN SKBI 2.3.26.1987 - Bakri, Muhammad Djaya (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2025)
Roads serve as critical infrastructure for enabling efficient, safe, and economical transportation of people and goods. Effective pavement planning must be based on methods suited to actual field conditions to ensure long-term functionality. The Road of Pantai Amal Lama, scheduled for construction in 2022, represents a new road segment requiring full construction from subgrade formation to surface layer. Given the relatively low traffic volume, the pavement design employs the Component Analysis Method outlined in SKBI 2.3.26.1987. This method primarily considers average daily traffic (ADT) and the California Bearing Ratio (CBR) of subgrade soil. Based on the analysis, the recommended layer thicknesses for a 10-year design life are: 10 cm sub-base, 20 cm base course, and 5 cm surface course. These structural dimensions form the technical basis for the road construction, aiming to ensure serviceability and durability under local conditions.